Ethanol-based solvent system for recovery antioxidant activity Centella asiatica L. Urban and its application in sleep-deprived Rats - Wardatun, Sri; Sofihidayati, Trirakhma; Afifah, Nida; Juhroh, Juju (Pharmaciana, 2024)
Antioxidants have the ability to eliminate free radicals by donating electrons to oxidants. Preclinical and clinical studies show that Centella asiatica L. Urban has antioxidant activity. Ethanol was the best solvent for extracted antioxidant compounds from Centella asiatica L. Urban. The concentration of ethanol solvents effect to the compounds extracted and its antioxidant activities. The objective of study to determine ethanol based solvent systems for best recovery of antioxidant activities and in vivo antioxidant activity of the most active extract using stress induced sleep-deprived rats with glutathione (GSH) concentration parameters. Ethanol based solvent system show different recovery antioxidant activity of Centella asiatica L. Urban. Ethanol 70% had the highest recovery of antioxidant activity with an IC50 value of 76.76 ppm. Ethanol 70% Centella asiatica L. Urban extract given in sleep-deprived rats at 300 mg/kg were not significantly different in glutathione levels from those group rats that received the positive control solution (ascorbic acid). The 70% ethanol extract of C. asiatica L. Urban has the potential to ameliorate the stress induced by sleep deprivation.